iNOS activity is necessary for the cytotoxic and immunogenic effects of doxorubicin in human colon cancer cells - Ghigo Dario (Molecular Cancer, 2009)
Abstract Background Doxorubicin is one of the few chemotherapeutic drugs able to exert both cytotoxic and pro-immunogenic effects against cancer cells. Following the drug administration, the intracellular protein calreticulin is translocated with an unknown mechanism onto the plasma membrane, where it triggers the phagocytosis of tumour cells by dendritic cells. Moreover doxorubicin up-regulates the inducible nitric oxide (NO) synthase (iNOS) gene in cancer cells, leading to huge amounts of NO, which in turn acts as a mediator of the drug toxicity and as a chemosensitizer agent in colon cancer. Indeed by nitrating tyrosine on the multidrug resistance related protein 3, NO decreases the doxorubicin efflux from tumour cells and enhances the drug toxicity. It is not clear if NO, beside playing a role in chemosensitivity, may also play a role in doxorubicin pro-immunogenic effects. To clarify this issue, we compared the doxorubicin-sensitive human colon cancer HT29 cells with the drug-resistant HT29-dx cells and the HT29 cells silenced for iNOS (HT29 iNOS-). Results In both HT29-dx and HT29 iNOS- cells, doxorubicin did not induce NO synthesis, had a lower intracellular accumulation and a lower toxicity. Moreover the drug failed to promote the translocation of calreticulin and the phagocytosis of HT29-dx and HT29 iNOS-cells, which resulted both chemoresistant and immunoresistant. However, if NO levels were exogenously increased by sodium nitroprusside, the chemosensitivity to doxorubicin was restored in HT29 iNOS-cells. In parallel the NO donor per se was sufficient to induce the exposure of calreticulin and to increase the phagocytosis of HT29 iNOS- cells by DCs and their functional maturation, thus mimicking the pro-immunogenic effects exerted by doxorubicin in the parental drug-sensitive HT29 cells. Conclusion Our data suggest that chemo- and immuno-resistance to anthracyclines are associated in colon cancer cells and rely on a common mechanism, that is the inability of doxorubicin to induce iNOS. Therefore NO donors might represent a promising strategy to restore both chemosensitivity and immunosensitivity to doxorubicin in resistant cells.